Syiah Isma’iliyah dan Syiah Itsna ‘Asyariah: (Pengertian, Konsep Imamah dan Ajaran Lainnya) - Aisyah Rahadianti Ratna Kemalasari (Jurnal Hukum Lex Generalis, 2022)
In the application of Islam by its ummah, there are two great teachings, namely the Sunni Sect and the Shi'ite Sect. Shi'ite sects are considered a cult in the application of Islam. As for this sect can be obtained and buried in several countries such as Iran which makes it the official flow of the country, Afghanistan, India, Pakistan, Syria, Lebanon, Greece, Britain, North America, China, and the Soviet Union. As for in this article, the author will discuss the flow of Shi'ite Isma'iliyah and Shi'ite Itsna 'Asyariah which are two of the most famous Shi'ite sects and spread in several countries mentioned earlier. The author will discuss the understanding, the concept of imamah, and the teachings embraced by the two sects of Shi'ite in detail and discuss the parts that are considered heretical in it.